Handbook of Industrial Chemistry and Biotechnology - Kent, James A.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2012)
Substantially revising and updating the classic reference in the field, this handbook offers a valuable overview and myriad details on current chemical processes, products, and practices. No other source offers as much data on the chemistry, engineering, economics, and infrastructure of the industry. The Handbook serves a spectrum of individuals, from those who are directly involved in the chemical industry to others in related industries and activities. It provides not only the underlying science and technology for important industry sectors, but also broad coverage of critical supporting topics. Industrial processes and products can be much enhanced through observing the tenets and applying the methodologies found in chapters on Green Engineering and Chemistry (specifically, biomass conversion), Practical Catalysis, and Environmental Measurements; as well as expanded treatment of Safety, chemistry plant security, and Emergency Preparedness. Understanding these factors allows them to be part of the total process and helps achieve optimum results in, for example, process development, review, and modification. Important topics in the energy field, namely nuclear, coal, natural gas, and petroleum, are covered in individual chapters. Other new chapters include energy conversion, energy storage, emerging nanoscience and technology. Updated sections include more material on biomass conversion, as well as three chapters covering biotechnology topics, namely, Industrial Biotechnology, Industrial Enzymes, and Industrial Production of Therapeutic Proteins.
Historical development of the chemical industry -- Chemical process safety: Safe practices and accident prevention -- Managing an emergency preparedness program -- Applied statistical methods -- Green engineering: Integration of green chemistry, pollution prevention, and risk based considerations -- Industrial catalysis: A practical guide -- Environmental chemical determinations -- Nanotechnology: Principles and applications -- Nanostructured materials: Industrial Applications -- Synthetic organic chemicals -- Chemistry in the pharmaceutical industry -- Manufactured textile fibers -- Dye application, manufacture of dyes and dye intermediates -- Chemistry of structural adhesives: Epoxy, urethane, and acrylic adhesives -- Synthetic resins and plastics -- Rubber -- The agrochemical industry -- Petroleum and its products -- Coal technology for power, liquid fuels and chemicals -- Natural gas -- The nuclear industry -- Synthetic nitrogen products -- Phosphorus and phosphates -- Fertilizers -- Sulfur and sulfuric acid -- Salt, chlor-alkali, and related heavy chemicals -- Industrial gases -- Wood and wood products -- Pigments, paints, polymer coatings, lacquers and printing inks -- Industrial biotechnology: Discovery to delivery -- Industrial enzymes and biocatalysis -- Industrial production of therapeutic proteins: Cell lines, cell culture and purification -- Biomass utilization -- Animal and vegetable fats, oils and waxes -- Sugar and other sweeteners -- Soap, fatty acids, and synthetic detergents -- Chemical explosives -- Electrochemical energy storage: Applications, processes, and trends.
Keywords: Chemistry; Biotechnology; Polymers; Chemical engineering; Electric engineering; Environmental pollution; Chemistry; Industrial Chemistry/Chemical Engineering; Biotechnology; Energy Technology; Industrial Pollution Prevention; Polymer Sciences